Conjoined twins in 2020 – state of the art and future directions. Issue 3 (June 2020) - Frawley, Geoff
Abstract : Purpose of review: A number of high profile conjoined twin separations have been extensively covered by the world media. Anaesthesia for conjoined twins is a procedure rarely experienced by paediatric anaesthetists. The increased survival of the twins has prompted discussion as to the most appropriate selection of patients, teams and hospitals to provide exceptional anaesthetic care. Recent findings: The number of conjoined twins presenting for surgery remains low with many infants not surviving foetal or early neonatal life. Anaesthetic management of less common conjoined infants such as craniopagus twins has highlighted the benefit of careful patient selection, extensive preoperative investigations and meticulous multidisciplinary team planning. The role of simulation of possible adverse perioperative events has been highlighted. Three dimensional anatomical models and virtual reality systems have permitted surgical planning in advance of actual intervention. A number of legal and ethical concerns have been reported especially in the setting of emergency separation where surgery is likely to contribute to death of one of the twins. Summary: There appears to be an expanding role for international teams with extensive separation experience becoming involved in international teleconferencing to improve patient management in low-resource countries. Whether the perioperative outcome is better when the conjoined twins are transferred to major centres for surgery or teams operate in the twin's country of origin remains to be seen.